Performance Data Visualization of Linux Events on Multicores - Scheer, Claudio; Hoffmann, Renato B.; Griebler, Dalvan; Manssour, Isabel H.; Fernandes, Luiz G. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2021: Anais do XXII Simpósio em Sistemas Computacionais de Alto Desempenho, 2021)
Profiling tools are essential to understand the behavior of parallel applications and assist in the optimization process. However, tools such as Perf generate a large amount of data. This way, they require significant storage space, which also complicates reasoning about this large volume of data. Therefore, we propose VisPerf: a tool-chain and an interactive visualization dashboard for Perf data. The VisPerf tool-chain profiles the application and pre-processes the data, reducing the storage space required by about 50 times. Moreover, we used the visualization dashboard to quickly understand the performance of different events and visualize specific threads and functions of a real-world application.